Point-of-contact interactive record linkage (PIRL) between demographic surveillance and health facility data in rural Tanzania. (2017) - Rentsch, Christopher T.; Reniers, Georges; Kabudula, Chodziwadziwa; Machemba, Richard; Mtenga, Baltazar; Harron, Katie; Mee, Paul; Michael, Denna; Natalis, Redempta; Urassa, Mark; Todd, Jim; Zaba, Basia
No abstract available